COMPUTER IMPLEMENTATION OF THE MODULE FOR THE CONNECTING ROD GROUP OF THE KDAM PROGRAM FOR THE DETERMINATION OF KINEMATIC AND DYNAMIC PARAMETERS - SHCHERBAN, VOLODYMYR; KOLISKO, OKSANA; MELNIK, GENADIJ; KOLISKO, MARJANA; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The computer module of the KDAM program for determining the kinematic and dynamic parameters of the connecting rod and rocker arm group of mechanisms of light industry machines allows you to determine the coordinates, velocity projections and accelerations of the center of mass of the connecting rod, rocker arm and the point of attachment of the links of the Asura groups to the connecting rod and rocker arm. During the dynamic analysis of the operation of the connecting rod and rocker arm group, the projections of the total reaction in the joints between the crank and the connecting rod, between the connecting rod and the rocker arm, and between the rocker arm and the fixed support are determined. The obtained results are used in the program to assess the intensity of technological processes of the light and textile industry when determining the change in the relative tension of the thread in the filling zones on the technological equipment. The development of a computer module for kinematic and dynamic analysis of lever mechanisms of light industry machines, which include connecting rod and rocker arm groups, allows to determine the parameters used in the program for assessing the intensity of technological processes of the light and textile industry when determining the change in the relative tension of the thread in the filling zones on the technological equipment Kinematic and dynamic analysis of flat mechanisms, which include connecting rod-rocker groups, plays a significant role in the design of new mechanisms and modernization of existing ones. The results of these studies can be used to calculate the strength of individual links, their inertial characteristics, optimization of structural parameters of mechanisms, and minimization of consumed energy. The objective function in the problem is the minimum necessary tension, which is the minimum sum of the angles covered by the thread of guide surfaces that have a cylindrical, elliptical shape, discrete segments of a straight line. The use of a computer program allows you to determine tensions and changes in relative tension in the filling zones of light and textile industry machines, which allows you to optimize the shape of the thread supply line even at the stage of designing the technological process. Thus, the topic of this article is relevant, which is important for assessing the intensity of technological processes of the light and textile industry when determining the change in the relative tension of the thread in the filling zones on the technological equipment.
Keywords: computer program module; kinematic parameters; dynamic parameters; connecting rod and rocker arm group